Characteristics of Public Green Open Spaces and Efforts In Enhancing The Quality and Function Using Tri-Valent Approach: Case of Manado City, Indonesia - Cynthia E.V Wuisang; Dwight M Rondonuwu; Rieneke L.E Sela; Sonny Tilaar; Suryono Suryono (Green Publisher Indonesia, 2023)
Urban communities can feel more applicable benefits in urban environmental planning as part of their daily activities. Urban public open spaces have not all considered the quality of the environment. Initial observations show that the utilization of public open space is not yet optimal from environmental and social aspects. Manado City Public open space is a place of interaction and recreation for the community, but currently little attention is paid to ecological or environmental functions and the quality of the landscape. With the observed background, this study aims to examine the city's public open spaces that can improve their functions and quality, by providing ecological protection and aesthetic quality of the landscape. This study evaluates the performance of open spaces (Patches Landscape) that support the sustainability of recent urban environment. The approach in this study in addition to sustainable cities, sustainable landscapes also integrate environmental psychology, aesthetics and people's perceptions of urban open spaces. This research also looks at the historical aspects of the community that will give identity to the planned open spaces, and their impact on improving the ecology and quality of open spaces. This research is conducted in Manado City, Indonesia. The method used in this research is a mix-method approach using Trivalent concept. The concept is to evaluate the tree-in-one main dimensions namely ecological, socio-cultural and aesthetic in landscape planning and design. The analysis of Landscape Quality Indicators is used to establish the concept of an engineering and spatial-based urban public open space design model recommendation.